A FOTOGRAFIA COMO REGISTRO DA HISTÓRIA DA EDUCAÇÃO: (RE)VIVENDO MEMÓRIAS DISCENTES - Brandão de Oliveira, Cristiana; Francisca Barros, Cristiana; Silva Moraes, Euleana; Pessoa de Oliveira, Gilvana (Revista Form@re - Parfor/UFPI, 2026)
.